2016
DOI: 10.4103/0970-9185.173372
|View full text |Cite
|
Sign up to set email alerts
|

Patient refusal for regional anesthesia in elderly orthopedic population: A cross-sectional survey at a tertiary care hospital

Abstract: Background and Aims:Improvements in pain management techniques in the last decade have had a major impact on the practice of orthopedic surgeries, for example, total hip arthroplasty and total knee arthroplasty. Although there are a number of treatment options for postoperative pain, a gold standard has not been established. In our institution, both general anesthesia and regional anesthesia (RA), are being offered to the elderly orthopedic population but RA is not frequently accepted by elderly population. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Postoperative back pain is frequently reported after RA. 35 It could be related to soft tissue damage during lumbar puncture. 36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Postoperative back pain is frequently reported after RA. 35 It could be related to soft tissue damage during lumbar puncture. 36 …”
Section: Discussionmentioning
confidence: 99%
“…Postoperative back pain is frequently reported after RA. 35 It could be related to soft tissue damage during lumbar puncture. 36 Hunger is a complex process involving neuronal and systemic components.…”
Section: Dovepressmentioning
confidence: 99%
“…Resistance to RA may sometimes be observed among surgeons[ 8 22 ] in developing countries which is in contrast to the studies done in developed countries where the orthopedic surgeons direct their patients to choose RA. [ 5 ] If a patients’ surgeon is against RA, the anesthesiologist will not be able to persuade him/her about RA.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some elder patients chose general anesthesia based on the recommendation of their surgeons (8). In a study conducted by Naik (17), it was demonstrated that younger patients are generally more knowledgeable about anesthesia than the older group of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A survey that was conducted in 2002, concluded that the two main reasons that regional anesthesia is not favored by surgeons includes delay in operating rooms and unpredictable success rate (7). Surgeon's choice of anesthesiology method has a great impact on patient's choice (8). On the other hand, patient refusal to go through regional anesthesia is an absolute contraindication and one should never coerce patients to go through the procedure against their will.…”
Section: Introductionmentioning
confidence: 99%